Analysis of Regional Stock Market Impact on Jakarta Composite Index using Markov - Riswanda, Cecep; Rikumahu, Brady (Penerbit Goodwood, 2025)
Purpose: In the current era of information, global stock market interconnections significantly influence investment decisions. Changes in one market rapidly affect others. The co-movement of stock markets presents challenges and opportunities for investors, whereas volatility spillovers complicate risk management and investment strategies. Research Methodology: This study examines the influence of the Nikkei 225, Straits Times Index, and Shanghai Composite Index on the Jakarta Composite Index across the pre-pandemic, pandemic, and post-pandemic phases. Results: Utilizing the hidden Markov model with regime-switching regression, this study identifies changes in market behavior due to economic shifts during the pandemic, revealing two regimes: synchronization and desynchronization. Conclusions: The N225 and STI indices have a consistently positive and significant influence on the JCI, whereas SCI shows a negative but statistically insignificant impact. During the pandemic (March 2020 to April 2021), market desynchronization increased, reducing the significance of N225 while STI remained impactful. Post-pandemic, synchronization improved, and both N225 and STI regained their significant influence on JCI, indicating strengthened regional market integration. Limitations: Pre-COVID-19, the Jakarta Composite Index shows strong synchronization with the Nikkei 225 and Straits Times Index, while the Shanghai Composite Index has an insignificant impact. During the COVID-19 pandemic, frequent desynchronization occurred due to high uncertainty and volatility, with only the Straits Times Index significantly influencing the Jakarta Composite Index. Contributions: This study contributes significantly to the understanding of regional stock market relationships and offers valuable insights for academia and practice.